2005
DOI: 10.1039/b500944h
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic, spectroscopic, computational and structural studies of some 13-vertex ruthenacarboranes

Abstract: Reduction of 1,2-closo-C2B10H12 followed by treatment with [RuCl2(p-cymene)]2(p-cymene = C6H4MeiPr-1,4) affords the 13-vertex ruthenacarborane 4-(p-cymene)-4,1,6-closo-RuC2B10H12, characterised both spectroscopically and, in two crystalline forms, crystallographically. Although asymmetric in the solid state, having a docosahedral cage architecture with cage C atoms at vertices 1 and 6, this species clearly has Cs symmetry on the NMR timescale at room temperature. However, the fluctional process in operation ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
29
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Very recently [7] we reported that room-temperature reduction (Na in THF) and metalation ([{Ru(p-cymene)Cl 2 } 2 ]) of 1,12-Ph 2 -1,12-closo-C 2 B 10 H 10 affords 1,6-Ph 2 -4-(p-cymene)-4,1,6-closo-RuC 2 B 10 H 10 (1) [8] as the major product instead of the expected 4,1,10-RuC 2 B 10 isomer. [6] We have now isolated and analyzed the two minor coproducts of this reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently [7] we reported that room-temperature reduction (Na in THF) and metalation ([{Ru(p-cymene)Cl 2 } 2 ]) of 1,12-Ph 2 -1,12-closo-C 2 B 10 H 10 affords 1,6-Ph 2 -4-(p-cymene)-4,1,6-closo-RuC 2 B 10 H 10 (1) [8] as the major product instead of the expected 4,1,10-RuC 2 B 10 isomer. [6] We have now isolated and analyzed the two minor coproducts of this reaction.…”
mentioning
confidence: 99%
“…The mechanisms by which [1,7- 2À might rearrange to the other isomers shown in Scheme 2 will be the subject of a future computational study. [13] We have previously shown that whilst compound 1 is resistant to isomerization in refluxing toluene, [8] at 180 8C it isomerizes to a mixture of 2 and 4. [7] In contrast, both 3 and 5 isomerize in refluxing toluene; 5 converts into 4, thus mirroring the behavior of its non-phenylated analogue, [6] whilst 3 isomerizes to 2, somewhat surprisingly in terms of the cage C···C separations (from crystallographic determinations) of 3.24 (3) and 2.79 (2).…”
mentioning
confidence: 99%
“…[21] As is common for 4,1,6-MC 2 B 10 species,t he anion in 1 is fluxional in solution at room temperature through ad ouble d-s-d process, [12] with NMR spectra revealing time-averaged C s symmetry.Aperspective view of the anion is shown in Figure 2. Salt 1 was fully characterized spectroscopically and crystallographically (see the Supporting Information).…”
mentioning
confidence: 99%
“…However, although we are fully confident that in 4 one cage Catom is at vertex 12, we have sought further evidence for the position of the second Catom through DFT calculations.Using DFT,the crystallographically determined skeleton was used to build ten isomers [2,7-Cp*-2,7,12,a-Ru 2 C 2 B 10 H 12 ](with a = 1, 3,4,5,6,8,9,11,13, and 14; a = 10 can be disregarded since that would be mirror-symmetric) and each isomer was optimized using the BP86 functional. Thus linear regression of the computed and experimental 11 BNMR shifts yields an R 2 value for the 2,7,1,12 isomer of 0.9954, compared with R 2 = 0.8676 for the next-best isomer (2,7,3,12). [20] In summary,t he isomer [2,7-Cp*-2,7,1,12-Ru 2 C 2 B 10 H 12 ]v ery clearly gave the best agreement between theory and experiment.…”
mentioning
confidence: 99%
“…It turns out that there is -we have serendipitously isolated and then structurally characterised three examples of 8,1,2-closo-MC2B9 species without C,C′ tethers, and consideration of the reactions in which these were formed together with their coproducts has led us to propose and then confirm a rational route to such species. Reduction (Na/THF, naphthalene [catalytic]) of 1,8-Ph2-4-(pcymene)-4,1,8-closo-RuC2B10H10, [8] followed by treatment with 0.5 equivalents of [Ru(-C6H6)Cl2]2 and work-up in air resulted in isolation of the known compounds 1,6-Ph2-4-(p-cymene)-4,1,6-closo-RuC2B10H10 [9] and 1,12-Ph2-4-(p-cymene)-4,1,12-closoRuC2B10H10, [8] the new 12-vertex species 1,2-Ph2-8-(p-cymene)-8,1,2-closo-RuC2B9H9 (1), the new 14-vertex diruthenacarborane 1-(p-cymene)-2,10-Ph2-14-(-C6H6)-1,14,2,10-closo-Ru2C2B9H9 (2) and the new 13-vertex diruthenacarborane 1,6-Ph2-4-(-C6H6)-5-(p-cymene)-4,5,1,6-closo-Ru2C2B9H9 (3) as well as partial recovery of the starting material.…”
mentioning
confidence: 99%